2022
DOI: 10.3389/fgene.2022.952836
|View full text |Cite
|
Sign up to set email alerts
|

N7-methylguanosine-related lncRNAs: Predicting the prognosis and diagnosis of colorectal cancer in the cold and hot tumors

Abstract: Background: 7-Methylguanosine(m7G) contributes greatly to its pathogenesis and progression in colorectal cancer. We proposed building a prognostic model of m7G-related LncRNAs. Our prognostic model was used to identify differences between hot and cold tumors.Methods: The study included 647 colorectal cancer patients (51 cancer-free patients and 647 cancer patients) from The Cancer Genome Atlas (TCGA). We identified m7G-related prognostic lncRNAs by employing the univariate Cox regression method. Assessments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Therefore, it is crucial to distinguish between cold tumors and hot tumors and convert the former into the latter. It has been reported that different clusters are related to different tumor immune microenvironments and can distinguish hot and cold tumors (29)(30)(31)(32). Therefore, we divided the patients into 2 clusters based on the R package CC, and the results indicated that the higher CD8 + T immune cells infiltration of cluster 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is crucial to distinguish between cold tumors and hot tumors and convert the former into the latter. It has been reported that different clusters are related to different tumor immune microenvironments and can distinguish hot and cold tumors (29)(30)(31)(32). Therefore, we divided the patients into 2 clusters based on the R package CC, and the results indicated that the higher CD8 + T immune cells infiltration of cluster 1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the important value of the risk score we established for tumor prognosis and systemic treatment, it cannot effectively identify hot and cold tumors. Several studies have proven that cluster analysis can be applied to distinguish hot and cold tumors and guide immunotherapy (29)(30)(31)(32). Based on the expression levels of Anoikis-Related lncRNAs, ccRCC patients were classified into two clusters using consensus clustering analysis (Figure 10A, Supplementary Figure 2).…”
Section: Unsupervised Cluster Analysis Distinguished Hot and Cold Tumorsmentioning
confidence: 99%
“…Although our risk model can predict patient prognosis and guide drug treatment, it cannot identify hot and cold tumours. Clusters can distinguish between hot and cold tumours and guide immunotherapy (52)(53)(54)(55). Therefore, we divided the patients into three clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Different immune microenvironments have different subtypes, resulting in different immunotherapy effects (50,51). Clusters can distinguish between hot and cold tumours and guide immunotherapy (52)(53)(54)(55). Therefore, we used the R package 'ConsensusClusterPlus' to group the patients into three clusters based on cluster analysis.…”
Section: Identifying Hot and Cold Tumours And Icis Sensitivitymentioning
confidence: 99%
“…They show potential value in predicting prognosis, drug sensitivity, and immunotherapy response in LIHC patients [ 196 ]. Seventeen m7G-related lncRNAs have also been reported in CRC, which can be used to predict prognosis in the clinical setting and to determine whether the tumor is cold or hot in CRC to improve the individualization of treatment [ 197 ]. In addition, there are similar studies in ESCC, UCEC, CM, and LUAD [ 198 201 ] as shown in Table 2 .…”
Section: Functions Of Lncrna-rna Modification In Different Types Of C...mentioning
confidence: 99%